Implementation and recommendation of postpartum visit methods during COVID-19 pandemic: a qualitative study from Indonesia - Wahyul Anis; Shrimarti R. Devy; Budi Prasetyo; Diah Indriani; Rize R. Amalia; Erni R. Dewi (AOSIS, 2023)
Background: The Maternal Mortality Rate (MMR) in Indonesia is still a health problem that must be solved. In 2018 and 2019, the postpartum period still dominates maternal mortality in Surabaya. The postpartum visit method is one of the essential things that can affect postpartum services, so it is necessary to evaluate the implementation of the postpartum visit method and recommend visiting methods to improve maternal health. Objective: The study explores the implementation and recommendation of postpartum visit methods during the COVID-19 Pandemic. Materials and Methods: It used a qualitative research type by assessing the interview and observation dept. The instruments used are questionnaires and observation sheets. Researchers conducted interviews with 14 mothers who had completed the postpartum period, five midwives, a stakeholder in the health office and two experts in the field of maternal health. The data is processed using organizing, reduction, coding, description, linking between themes, and data interpretation. Results: Offline visits to health facilities still dominate the implementation of the postpartum visit method. The recommended postpartum visit method combines visits to health facilities, home visits, and telehealth. Besides that, it is necessary to consider maternal postpartum services up to 3 months after delivery, especially for postpartum mothers who have problems. Conclusion: The postpartum visit method during the COVID-19 pandemic, has not run optimally because there are restrictions on offline visits. However, it has not been supported by online monitoring or home visits.